Midwifery Care for a Third-Trimester Pregnant Woman with Moderate Anemia: A Case Study - Hasnah, Azizah; Hia, Desti Nurani; Feliany, Chindy; Manurung, Basaria; Hasibuan, Sari Donni (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Anemia during pregnancy is one of the most common health problems, particularly in the third trimester, due to the increased iron requirements for fetal growth and maternal blood volume expansion. If left untreated, anemia may lead to various maternal and fetal complications. This article aims to describe midwifery care for a third-trimester pregnant woman with moderate anemia using Varney’s Midwifery Management approach. The method used was a case study of Mrs. A, a 28-year-old G2P1A0 woman at 32 weeks of gestation who presented with complaints of fatigue, dizziness, weakness, and palpitations. Physical examination revealed pale conjunctiva, and laboratory results showed a hemoglobin level of 9.8 g/dL, indicating moderate anemia. Midwifery care included health education regarding anemia, counseling on iron-rich foods, administration of iron (Fe) tablets, adequate rest, and regular antenatal monitoring. Evaluation after two weeks showed improvement in the mother's condition, reduced symptoms, and an increase in hemoglobin level to 10.8 g/dL. In conclusion, comprehensive midwifery care through education, nutritional improvement, and adherence to iron supplementation can effectively improve hemoglobin levels and help prevent maternal and fetal complications.